Estimates of terms in Ohm's law during an encounter with an electron diffusion region - R. B. Torbert; J. L. Burch; B. L. Giles; D. Gershman; C. J. Pollock; J. Dorelli; L. Avanov; M. R. Argall; J. Shuster; R. J. Strangeway; C. T. Russell; R. E. Ergun; et al. (Geophysical Research Letters)
Abstract We present measurements from the Magnetospheric Multiscale (MMS) mission taken during a reconnection event on the dayside magnetopause which includes a passage through an electron diffusion region (EDR). The four MMS satellites were separated by about 10 km such that estimates of gradients and divergences allow a reasonable estimate of terms in the generalized Ohm's law, which is key to investigating the energy dissipation during reconnection. The strength and character of dissipation mechanisms determines how magnetic energy is released. We show that both electron pressure gradients and electron inertial effects are important, but not the only participants in reconnection near EDRs, since there are residuals of a few mV/m (~30–50%) of E + Ue × B (from the sum of these two terms) during the encounters. These results are compared to a simulation, which exhibits many of the observed features, but where relatively little residual is present.